Les misérables (2012) [videorecording (DVD)] - Crowe, Russell, 1964-; Jackman, Hugh; Hathaway, Anne, 1982-; Seyfried, Amanda; Redmayne, Eddie, 1982-; Tveit, Aaron; Barks, Samantha; Allen, Isabelle, 2002-; Huttlestone, Daniel, 1999-; Wilkinson, Colm; Bonham Carter, Helena, 1966-; Baron Cohen, Sacha, 1971-; et al. (Universal Studios Home Entertainment, 2013)
Suggestive and sexual material, violence and thematic elements.